Characterization of Heat-Inducible Expression and Cloning of HtpG (Hsp90 Homologue) of Porphyromonas gingivalis - Lopatin, Dennis E. (American Society for Microbiology, 2000)
Porphyromonas gingivalis is implicated in the etiology of periodontal disease. Associations between microbial virulence and stress protein expression have been identified in other infections. For example, Hsp90 homologues in several microbial species have been shown to contribute to virulence. We previously reported that P. gingivalis possessed an Hsp90 homologue (HtpG) which cross-reacts with human Hsp90. In addition, we found that elevated levels of serum antibody to Hsp90 stress protein in individuals colonized with this microorganism were associated with periodontal health. However, the role of HtpG in P. gingivalis has not been explored. Therefore, we cloned the htpG gene and investigated the characteristics of HtpG localization and expression in P. gingivalis. htpG exists as a single gene of 2,052 bp from which a single message encoding a mature protein of approximately 68 kDa is transcribed. Western blot analysis revealed that the 68-kDa polypeptide was stress inducible and that a major band at 44 kDa and a minor band at 40 kDa were present at constitutive levels. Cellular localization studies revealed that the 44- and 40-kDa species were associated with membrane and vesicle fractions, while the 68-kDa polypeptide was localized to the cytosolic fractions.